2003
DOI: 10.1143/jjap.42.6477
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Giant Piezoelectric Properties in the [001] Domain Engineered Relaxor Single Crystals

Abstract: Relaxor single crystals PZN-9%PT have been cut and poled along [ 1 101] direction for which the spontaneous polarization P s is approximately parallel to the poling field E p . The piezoelectric matrix of the monoclinic single-domain (1M state) has been determined, in the approximation of an orthorhombic symmetry. The shear mode (15) along [101], gives the highest electromechanical coupling factor k 15 (>80%) and the largest piezoelectric coefficient d 15 ($3200 pC/N). The properties of the disoriented 1M stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 12 publications
(21 reference statements)
1
32
0
Order By: Relevance
“…The final PUMA prototype made of PZN-PT showed a charge sensitivity of 75 pC/g and a resonance frequency of 19.4 kHz [65]. This work demonstrated that the first generation relaxor-PT crystals can be integrated into the novel accelerometer design for significantly improved signal-to-noise ratio (greater than 15 dB) by taking advantages of their high d 33 and d 31 [64].…”
Section: Unimorph Accelerometermentioning
confidence: 86%
See 2 more Smart Citations
“…The final PUMA prototype made of PZN-PT showed a charge sensitivity of 75 pC/g and a resonance frequency of 19.4 kHz [65]. This work demonstrated that the first generation relaxor-PT crystals can be integrated into the novel accelerometer design for significantly improved signal-to-noise ratio (greater than 15 dB) by taking advantages of their high d 33 and d 31 [64].…”
Section: Unimorph Accelerometermentioning
confidence: 86%
“…Over the last two decades, relaxor-based ferroelectric single crystals such as Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 (PMN-PT) and Pb(Zn 1/3 Nb 2/3 )O 3 -PbTiO 3 (PZN-PT) have been spotlighted due to their ultrahigh piezoelectric properties [22,23]. For example, the ultra-high longitudinal piezoelectric strain coefficient d 33 (>2000 pC/N) and electromechanical coupling factor k 33 (>0.9) of the relaxor-PT single crystals far outweigh the mostly used polycrystalline ceramics Pb(Zr,Ti)O 3 (PZT), and these merits are promising for a broad range of electromechanical applications [24,25].…”
Section: Relaxor-pt Ferroelectric Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 Similar calculations have shown that intrinsic piezoelectric anisotropy accounts for at least 50% of the piezoelectric response of ͓001͔ C -poled, domain-engineered PZN-9PT. 34 Thus, a majority intrinsic contribution to the direct piezoelectric response of ͓001͔ C -poled PZN-4.5PT and PZN-8PT might be expected. Moreover, the intrinsic contribution, as measured along the non polar ͓001͔ C poling direction of each domain-engineered crystal, is also expected to increase as the first order ferroelectric-ferroelectric phase transition is approached.…”
Section: -4mentioning
confidence: 99%
“…Following the rediscovery of their very high piezoelectric coefficients for rhombohedral or orthorhombic compositions oriented along the nonpolar ͓001͔ C ͑C: pseudocubic͒ direction, 1 much work has concentrated on the concept of domain engineering 2 not only in these materials [3][4][5][6][7] but in simpler perovskite crystals as well. [8][9][10] A good definition of "domain engineering" is that given by Bell: 2 A domain-engineered crystal is one which has been poled by the application of a sufficiently high field along one of the possible polar axes of the crystal other than the zerofield polar axis, creating a set of domains in which the polarizations are oriented such that their angles to the poling direction are minimized.…”
Section: Introductionmentioning
confidence: 99%